Fabricated Optical Strip Waveguide of Nanophotonics Lithium Niobate - Makram A. Fakhri; Y. Al-Douri; U. Hashim (IEEE Photonics Journal)
The fabrication of an optical waveguide by designing the device and using a positive photoresist via photo lithography (ultraviolet light) to transfer the pattern of the sample has been studied. A direct coupler method was used to investigate a different wavelength pointer laser beam coupled with a fiber–fiber test coupling coupler employing different wavelength lasers ≈5 mW to measure propagation loss and lattice mismatch. The speed of light and numerical aperture were correlated with refractive index. The result showed a good efficiency of laser transfer to fabricate the optical waveguide.